Ink girls - Nijkamp, Marieke (Greenwillow Books, Harper Alley, an Imprint of HarperCollins Publishers, 2023)
Eleven-year-old Cinzia is a printer's apprentice. She adores Mestra Aronne for taking her in--most guilds don't have room for apprentices with a crippled leg--and she loves life in the raggedy workshop that smells of paper and printing, where secrets and stories are always circulating. So when Mestra Aronne is imprisoned for publishing accusations against the ruling family, Cinzia will do anything to prove that Mestra Aronne only told the truth. Elena is the exact same age as Cinzia, but she's forced to keep to her rooms and garden. To protect her, according to her mother. To protect the city, according to her uncle. Because Elena is not the charming, powerful noble her family wants her to be. According to them, she doesn't communicate well. She's too gullible and literal and struggles to understand other people. After unexpectedly meeting face-to-face, the girls follow a trail of clues through their golden city, drawing supporters and learning more about their home and each other than they ever could have imagined. If one person--no matter how young--can change the course of history, just imagine what a whole flock of them could do" --